Resolving bank failures and institutions - Rawlins, Marlon,Zanforlin, Luisa (International Monetary Fund, 2021)
Policymakers across countries have been seeking to strengthen the institutional framework to control fiscal costs and feedback effects to the real economy generated by bank failures. On a cross-section of countries, we find evidence that suggests that bank supervisors' intervention in bank failures may be positively associated with some aspects of the administrative and regulatory framework. Our results appear to hold also during times of financial instability. Finally, we find some evidence that the same institutional features may be associated with lower fiscal outlays during banking crises
10.5089/9781513590837.001
Keywords: Graue Literatur; Financial Economics; Banking Crisis; Administrative Law; Bankrupcy; Bank Regulation and Supervision; Financial Institutions and Services; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Financial Risk Management; Finance: General; Macroeconomics; Economics: General; Banks and Banking; Industries: Financial Services; Financial Institutions and Services: Government Policy and Regulation; Regulated Industries and Administrative Law; Financial Crises; Financial Institutions and Services: General; Central Banks and Their Policies; General Financial Markets: Government Policy and Regulation; Economic & financial crises & disasters; Economics of specific sectors; Finance; Banking; Banking crises; Distressed institutions; Financial institutions; Central bank autonomy; Central banks; Financial sector stability; Financial sector policy and analysis; Currency crises; Informal sector; Economics; Financial crises; Financial services industry